Pemahaman Literasi Informasi Halal Siswa : Literasi Halal Berdasarkan Berdasarkan Model Literasi Informasi Big Six - Priyatna Hendriawan; Ade Yeti Nuryantini; Tri Cahyanto; Neneng Windayani (Universitas Alma Ata, 2025)
In the digital era characterized by easy access to information, the ability to filter and understand valid information has become an essential skill in the 21st century. Information literacy, involving the ability to seek, evaluate, and effectively use information, also serves as a foundation in ensuring the halalness of products and services amidst the rapid flow of digital information. This study aims to analyze the level of halal information literacy among junior high school (SMP) students in West Bandung Regency based on the information literacy indicator model developed by the researcher. The research employs a mixed-method approach with a quantitative-qualitative design. Quantitative data were collected through closed-ended questionnaires and analyzed using descriptive statistics, while qualitative data were gathered through open-ended questionnaires and processed by identifying response patterns. The sample comprised 30 junior high school students selected through purposive sampling. The findings indicate that students’ halal information literacy falls into the moderate category, with a relatively good understanding at the stage of recognizing halal information sources. However, weaknesses were found in their ability to evaluate and utilize halal information effectively. Qualitative data reveal that students demonstrate high interest in halal information literacy but face challenges in identifying the halalness of products due to limited access to information and insufficient in-depth knowledge. This study contributes by developing halal information literacy indicators that can serve as a reference for assessing and improving halal literacy among students. These findings also form the basis for designing more comprehensive halal literacy education strategies in schools.